Evaluation of soil quality in a reforested forest with eucalyptus in the area of Pacán - Huánuco 2017 - Diaz-Jorge, Hanonver J. (2019)
The present research work, entitled "Evaluation of the soil quality in a reforested forest with eucalyptus in the Pacán - Huánuco 2017 area", had as its general objective: To evaluate the soil quality in a forest reforested with eucalyptus and as specific objectives : Determine the nutrients that the forest contributes reforested with eucalyptus to the soil; Determine the physical characteristics of reforested soils with eucalyptus and Describe the physico - chemical differences between the reforested forest floor in the Pacán area with a non - reforested soil. For the present study, a plantation of Eucalyptus globulus was selected, where 15 sub-samples of reforested soil with eucalyptus Eucalyptus globulus and 15 sub-samples were extracted in nonreforested soil, according to the methodology for sampling. According to the results obtained from the laboratory of the Agrarian University of La Molina, it was determined that the reforested forest represented by sample number 1 (M1), has a pH 7.12, organic matter 5.63%, Nitrogen 0.25%, Phosphorus 3.3 ppm, Potassium 62 ppm, of the mechanical analysis of soil is within the textural classification Sandy Sand, while the soil without vegetation, represented by sample 2 (M2) were: pH 8.24, organic matter 1.77%, Nitrogen 0.07, Phosphorus 2.2 ppm, Potassium 156 ppm, of the mechanical analysis of soil is within the textural classification Franco Arcilloso. So it is recommended to reforest the Huánuco hillsides with this species because it improves the pH by making it more neutral, increases the content of organic matter and therefore nitrogen.